2017
DOI: 10.1038/s41598-017-01688-2
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-created rich properties in grapheme nanoribbons: Chemical bondings

Abstract: The alkali-adsorbed graphene nanoribbons exhibit the feature-rich electronic and magnetic properties. From the first-principles calculations, there are only few adatom-dominated conduction bands, and the other conduction and valence bands are caused by carbon atoms. A lot of free electrons are revealed in the occupied alkali- and carbon-dependent conduction bands. Energy bands are sensitive to the concentration, distribution and kind of adatom and the edge structure, while the total linear free carrier density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
(200 reference statements)
0
5
0
Order By: Relevance
“…Very interesting, an extension of DSC, a modulated differential scanning calorimeter [72,73], is further developed to provide the more reliable [77,80] and lattice specific heat [?]. The previous experiments clearly show that the former presents a linear T-dependence at very low temperature [T < 1.2 K; [77]], and the latter follows the T 3 law at low temperature and approximately T 2 law at higher temperature [78]. The applications of graphite systems promise an economical way to a new class of efficient thermal management materials, such as, the relatively high thermal conductivities very suitable for thermal interface applications [81,82].…”
Section: Ter/laser Flash Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…Very interesting, an extension of DSC, a modulated differential scanning calorimeter [72,73], is further developed to provide the more reliable [77,80] and lattice specific heat [?]. The previous experiments clearly show that the former presents a linear T-dependence at very low temperature [T < 1.2 K; [77]], and the latter follows the T 3 law at low temperature and approximately T 2 law at higher temperature [78]. The applications of graphite systems promise an economical way to a new class of efficient thermal management materials, such as, the relatively high thermal conductivities very suitable for thermal interface applications [81,82].…”
Section: Ter/laser Flash Analysismentioning
confidence: 92%
“…The diverse physical phenomena, including the semiconductors, semimetals and metals the absence or recovery of the Dirac-cone structures [73], the linear, parabolic and oscillatory energy dispersions [74], the critical points in the energy-wave-vector space [the minima, maxima and saddle points; Ref. [36]], the semiconductor-metal transition [75,76], the creation of band gap [77], and non-magnetic, ferromagnetic or anti-ferromagnetic spin configurations [78], are clearly explained by the concise physical and chemical pictures. The close associations of the firstprinciples calculations and the generalized tight-binding model will be very useful for the emergent 2D materials in exploring the various magnetic quantization phenomena.…”
Section: Future Perspectives and Open Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the DFT calculations, the n-type adsorption effects of the alkali atoms on GNRs were revealed by Y. T. Lin et al, in which the optimal adsorption sites of the alkali atoms were found to be on the hollow sites of GNRs and the alkali-adsorbed systems become n-type metals with a high free electron density. 42 In terms of the adatom substitutions, the host atoms are directly replaced by guest atoms (adatoms) in the same host system, creating guest adatom-host atom bonds, in which the induced adatom-atom bonds significantly modify the geometric structures as well as the fundamental properties. 43,44 Consequently, the properties of the host system are significantly enriched by different kinds of adatoms, while the adatom concentrations and distributions are the main factors tuning the essential properties.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic and magnetic properties could be dramatically changed by the chemical modifications. The previous works predict that the alkali adatom adsorptions on GNRs create conduction electrons (n-type doping) and diversify zigzag-edge magnetic configurations 18 . However, fluorinated GNRs present the nonmagnetic semiconducting behavior except that certain low-concentration distributions belong to the p-type metal.…”
Section: Introductionmentioning
confidence: 99%